Impact of dimethylsulfide chemistry on air quality over the Northern Hemisphere. (1st January 2021) - Zhao, Junri; Sarwar, Golam; Gantt, Brett; Foley, Kristen; Henderson, Barron H.; Pye, Havala O.T.; Fahey, Kathleen M.; Kang, Daiwen; Mathur, Rohit; Zhang, Yan; Li, Qinyi; Saiz-Lopez, Alfonso
Abstract: We implement oceanic dimethylsulfide (DMS) emissions and its atmospheric chemical reactions into the Community Multiscale Air Quality (CMAQv53) model and perform annual simulations without and with DMS chemistry to quantify its impact on tropospheric composition and air quality over the Northern Hemisphere. DMS chemistry enhances both sulfur dioxide (SO2 ) and sulfate ( SO 4 2 − ) over seawater and coastal areas. It enhances annual mean surface SO2 concentration by +46 pptv and SO 4 2 − by +0.33 μg/m 3 and decreases aerosol nitrate concentration by −0.07 μg/m 3 over seawater compared to the simulation without DMS chemistry. The changes decrease with altitude and are limited to the lower atmosphere. Impacts of DMS chemistry on SO 4 2 − are largest in the summer and lowest in the fall due to the seasonality of DMS emissions, atmospheric photochemistry and resultant oxidant levels. Hydroxyl and nitrate radical-initiated pathways oxidize 75% of the DMS while halogen-initiated pathways oxidize 25%. DMS chemistry leads to more acidic particles over seawater by decreasing aerosol pH. Increased SO 4 2 − from DMS enhances atmospheric extinction while lower aerosol nitrate reduces the extinction so that the net effect of DMS chemistry on visibility tends to remain unchanged over most of the seawater. Highlights: Dimethylsulfide enhances sulfate over seawater and coastal areas. The impact of dimethylsulfide on sulfate is the largest in the summer. Hydroxyl and nitrate radical-initiated pathways oxidize 75% and halogen-initiated pathways oxidize 25% of dimethylsulfide. Dimethylsulfide leads to more acidic particles.